2017
DOI: 10.4103/ijdr.ijdr_79_15
|View full text |Cite
|
Sign up to set email alerts
|

Determination of p16 overexpression as an indicator of human papillomavirus infection in oral dysplasia and carcinoma

Abstract: p16 immunostaining is a good first-line assay for eliminating HPV-negative cases from additional analysis, but other causes of p16 overexpression in oral tumorigenesis related to tobacco consumption in keratinizing squamous cell carcinoma needs to be explored further.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 0 publications
0
6
1
Order By: Relevance
“…In line with this, we found that p16 was more often overexpressed in OL with dysplasia. The sensitivity was 29% and the specificity 84%, which differs from the 83% sensitivity and 40% specificity reported by Pathak et al (50).…”
Section: Discussioncontrasting
confidence: 81%
“…In line with this, we found that p16 was more often overexpressed in OL with dysplasia. The sensitivity was 29% and the specificity 84%, which differs from the 83% sensitivity and 40% specificity reported by Pathak et al (50).…”
Section: Discussioncontrasting
confidence: 81%
“…p16 INK4a expression detection by IHC was performed in five serial sections of 5 μm FFPE tissue as per Klaes et al and detection was performed as per BioGenex manufacturer's protocol (Catalog # QD400, BioGenex, CA). All the sections showing either strong nuclear and/or cytoplasmic immunostaining were considered positive and graded qualitatively according to the following arbitrary scale: 0 (no positive staining), +1 (<10% cells showing positive staining), +2 (>10% but <50% positive staining), and +3 (>50% positive staining) …”
Section: Methodsmentioning
confidence: 99%
“…Of several genotypes, HPV 16 is the most prevalent subtype of HPV, commonly affects the younger age groups with male predisposition . p16 immunostaining has been considered as the first‐line assay in the detection of HPV‐induced cancers . However, polymerase chain reaction (PCR) amplification has been considered as the gold standard technique in the detection of HPV DNA in OSCC cases; it offers advantages such as high sensitivity and type‐specific and formalin‐fixed paraffin‐embedded (FFPE) tissue acceptances .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…(13) Several studies have validated high degree of association of HPV infection and p16 expression suggesting that p16 can be used as a surrogate marker for high risk HPV in oral squamous cell carcinomas. (14)(15)(16) In this study, we aimed to determine the prevalence of HPV in patients with oral and oropharyngeal carcinoma at a tertiary care hospital in Central India using p-16 as a surrogate marker of high-risk HPV infection. Additionally, association of p-16 immunoexpression with clinicopathological characteristics, namely, age, sex and histological type/grade of cancer was established.…”
mentioning
confidence: 99%